Penerapan Pengawasan Konservasi Satwa Kelelawar Secara Mandiri - Nibras Karnain Laya; Safriyanto Dako; Fahria Datau; Suparmin Fathan; Stevandi Sampow; Ismail Baderan (Univeristas Negeri Gorontalo, 2021)
Supervision of the conservation of bat animals in ensuring the preservation of bat animals and economic stability for the beneficiary groups. The purpose of the service is to implement independent supervision of bat conservation. Conservation monitoring activities are carried out in the Bat Conservation area in Olibu Village, Paguyaman Pantai District, Boalemo Regency. The target group is the Bat Utilization Group and the community. Service activities are focused on increasing group and community understanding of supervisory understanding (1). Designing an independent conservation monitoring model focused on monitoring the fishing process and monitoring conservation areas (2). Monitoring line (3). The initial assessment illustrates that the group's understanding of the importance of supervision is still low at 9.95% before receiving material delivery. The final assessment illustrates that there is an increased understanding of knowledge about the self-monitoring model that will be applied in conservation areas by 82.93%. Supervision activities on the management of bat animal capture are comprehensive supervision, starting from the time the catching is carried out until the bats are marketed. Supervision during capture is needed in order to stabilize the protection and survival of captured bats, especially for animals that are not fit to be caught and traded. Supervision of Conservation Areas is the right step to take in preserving bat animals and economic stability for groups using bats, in addition to existing conservation areas, they can develop into tourist areas. There are 2 bat control lines and a conservation area, namely land and sea routes. The monitoring model for bat conservation independently can be realized by involving groups of users, the village community as the object of supervision over the activities of monitoring the capture management process and supervision of conservation areas, while the Olibu village government as a supervisory control through implementation.